Resolving contestation through discursive engagement: towards the contextual diffusion of EU rule of law norms?. Issue 3 (3rd July 2018) - Webb, Jonathan
ABSTRACT: Rule of law reform is a key feature of the European Union's (EU) enlargement policy towards the Western Balkans. However, associated rule of law norms can be contentious. This article considers the role discursive engagement plays in aiding the diffusion of contested rule of law norms. It highlights the role discursive engagement plays in overcoming points of contestation and facilitating the contextual diffusion of rule of law norms. This conceptual argument is substantiated by assessing rule of law reforms in an EU Candidate State, Serbia. Within this case study, four internal cases are outlined. Two of these cases demonstrate the failure of rule of law norms to contextualize in the absence of meaningful discursive engagement. The other two cases demonstrate the role discursive engagement can play in helping to promote norm contextualization.